Renal cell cancer: overview of the current therapeutic landscape. Issue 9 (1st September 2016) - Erman, Mustafa; Benekli, Mustafa; Basaran, Mert; Bavbek, Sevil; Buyukberber, Suleyman; Coskun, Ugur; Demir, Gokhan; Karabulut, Bulent; Oksuzoglu, Berna; Ozkan, Metin; Sevinc, Alper; Yalcin, Suayib
ABSTRACT: Introduction : The last decade has witnessed dramatic improvements in the diagnosis, classification and treatment of renal cell cancer (RCC). Besides improvements in surgical techniques in early stages, introduction of novel targeted agents has resulted in improved outcomes in advanced RCC for which no effective treatment existed until recently. Areas covered : This article reviews epidemiology, pathology and pathogenesis, diagnosis, clinical staging, prognostic factors and treatment modalities of early stage and advanced RCC. Expert commentary : Although treatment options are expanding rapidly, practicing physicians face considerable challenges in the decision-making process. Therapeutic agents may have unique side effects and unexpected drug interactions. RCC represents one of the major success stories of clinical oncology in recent years and the progress appears to be far from having reached a plateau. We aim to present a comprehensive in-depth review of RCC in an attempt to provide evidence-based recommendations and future perspectives for practicing oncologists.